MICROPLASTIC ACCUMULATION IN ECONOMICALLY IMPORTANT FISH SPECIES FROM BARRANGLOMPO ISLAND WATERS, MAKASSAR (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Microplastics (MPs) have been found in various marine compartments especially in fish, and there is limited information regarding the accumulation of MPs in fish organs. Therefore, this study aimed to investigate the presence of microplastics in economically important fish organs (Hemiramphus far, Siganus virgatus, and Lethrinus lentjan) at Barranglompo Island Waters, Makassar, and also to identify the characteristics of microplastics including color, shape, and size. Each organ was extracted using KOH 20% and the MPs characteristics were observed visually using a stereomicroscope. The result showed that MPs were found in gills, gastrointestinal tract, and flesh of three fish species. The detection rate of MPs in H. far, S. virgatus, and L. lentjan was 100%, 100%, and 82%, respectively. The most common MP color was blue, the shape was predominantly line, and the most abundant size range was 1–5 mm. Further studies are needed to investigate the accumulation of MPs in fish organs experimentally in the laboratory.